Students’ Perception of Using Multimodal “E-Book” for Learning Writing Descriptive Text at Junior High School Level - Maufiroh, Faikotul; Rini Listyowati; Ina Daril Hanna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Multimodal E-Book is a learning media that can be used in learning writing descriptive text. This research aims to explores the students’ perception of using multimodal E-Book media for learning writing descriptive text. This research used narrative inquiry research design. The subjects in this research is the eight grade students of MTs Tarbiyatus Shibyan Wal Banat which consisting of 19 students with 10 students selected to interviewed. The data were collected through observation, interview and documentation. Then, analyzed used descriptive qualitative. The result showed that students generally have positive perception of multimodal E-Book, as it make learning more engaging, interesting and facilitate a better understanding of the material compared to the conventional learning method. Additionally, the advantages include improved students understanding, increased enthusiasm for learning, enhanced vocabulary, and better pronounciation skills. However, challenges were also identified, such as difficulties using media independently at school due to limited of digital access at school. Additionally, students struggled in understanding the contents of multimodal E-Book that was entirely in English without Indonesian translation. Apart form that the overall impact remains positive, indicating that multimodal E-Book are effective strategy to support learning writing descriptive text.